2023
DOI: 10.1093/infdis/jiad058
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-Mpox Virus Activity of Atovaquone, Mefloquine, and Molnupiravir, and Their Potential Use as Treatments

Abstract: Background Mpox virus (MPXV) is a zoonotic orthopoxvirus and caused an outbreak in 2022. Although tecovirimat and brincidofovir are approved as anti-smallpox drugs, their effects in mpox patients have not been well documented. In this study, by a drug repurposing approach, we identified potential drug candidates for treating mpox and predicted their clinical impacts by mathematical modeling. Methods We screened approved 132 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Proposed mechanisms for the antiviral effect of mefloquine against coronaviruses and other viruses such as Ebola and monkeypox virus include the inhibition of viral uptake by endocytosis and plasma membrane fusion and release of the viral genome from endosomes; however, a molecular basis for the mechanism is not reported (Akazawa et al, 2023;Sacramento et al, 2022;Shionoya et al, 2021). In fact, MFQ's effect on endocytosis has not been studied extensively in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed mechanisms for the antiviral effect of mefloquine against coronaviruses and other viruses such as Ebola and monkeypox virus include the inhibition of viral uptake by endocytosis and plasma membrane fusion and release of the viral genome from endosomes; however, a molecular basis for the mechanism is not reported (Akazawa et al, 2023;Sacramento et al, 2022;Shionoya et al, 2021). In fact, MFQ's effect on endocytosis has not been studied extensively in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent screening of a library of approved drugs against MPXV in cytopathic effect assay identified atovaquone ( 145 ), mefloquine ( 146 ), and molnupiravir ( 147 ) as hits with IC 50 values of 0.52, 5.19, and 1.35 μM, respectively (Figure ). The IC 50 values for the positive controls tecovirimat ( 1 ) and cidofovir ( 3 ) were 2.80 nM and 13.7 μM, respectively. Drug time-of-addition experiment showed that mefloquine inhibited viral entry, while atovaquone and molnupiravir targeted postentry processes.…”
Section: Antivirals Against Orthopoxvirusesmentioning
confidence: 98%
“…Follow-up studies uncovered their antiviral activity against VACV and VARV (Figure 14). 169,170 Isatin-βthiosemicarbazone (IBT, 158) and marboran (159) inhibited CPXV (Brighton) and six VACV strains in cell culture. 171 Both compounds were highly effective in treating VACV-IHD virusinfected BALB/c mice when dosed by intraperitoneal injection at up to 72 h postinfection.…”
Section: Virucidal Compoundsmentioning
confidence: 99%
“…An in vitro screen of 132 clinically approved drugs identified atovaquone, mefloquine, and molnupiravir with efficacy against MPXV. 52 Supportive and symptomatic care, which may be the only resources available for patients in resource-limited settings, play an important role in the management of monkeypox. Pain management is key and requires topical agents, oral medications, or nerve blocks.…”
Section: Managementmentioning
confidence: 99%
“…Thus, tecovirimat, brincidofovir, and cidofovir may be effective in the treatment and short-term prophylaxis of smallpox and related poxvirus infections in humans. An in vitro screen of 132 clinically approved drugs identified atovaquone, mefloquine, and molnupiravir with efficacy against MPXV …”
Section: Managementmentioning
confidence: 99%